Toughness evaluation of hard coatings and thin films - Zhang, Sam (2013)
Enormous progress has been achieved over the past decade in evaluating the toughness of hard coatings and thin films. This paper reviews methodologies developed based on indentation, bending, and microtensile testing. In addition, we discuss a recent development in fracture toughness measurement which involves the application of macrotension to a substrate in order to induce microtension in a patterned thin film.